2007
DOI: 10.2217/17460751.2.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Multipotential Mesoangioblast Stem Cell Therapy in the Mdx/Utrn -/- mouse model for Duchenne muscular dystrophy

Abstract: Mesoangioblasts differentiate into multiple cell types damaged during the progression of severe muscle disease and protect fibers from damage. As such, they are good candidates for therapy of Duchenne muscular dystrophy and perhaps other neuromuscular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 60 publications
6
49
1
1
Order By: Relevance
“…Interestingly, this contribution to the regenerated fibers, delayed with regard to the systemic delivery, could promote ongoing repair of dystrophic muscle. 85 Recently, a marked improvement of muscle performance was measured in both respiratory and cardiac muscles of mdx mice following treatment with halofuginone, a collagen synthesis inhibitor that prevented fibrosis. 86,87 By demonstrating the key role of fibrosis on muscle function alterations in a dystrophic context, these findings support the hypothesis that the major restriction in endomysial expansion observed in the muscles of our treated GRMD dogs might have a direct impact on their walking ability and largely contribute to their clinical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this contribution to the regenerated fibers, delayed with regard to the systemic delivery, could promote ongoing repair of dystrophic muscle. 85 Recently, a marked improvement of muscle performance was measured in both respiratory and cardiac muscles of mdx mice following treatment with halofuginone, a collagen synthesis inhibitor that prevented fibrosis. 86,87 By demonstrating the key role of fibrosis on muscle function alterations in a dystrophic context, these findings support the hypothesis that the major restriction in endomysial expansion observed in the muscles of our treated GRMD dogs might have a direct impact on their walking ability and largely contribute to their clinical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The mdx/utrn Ϫ/Ϫ mice lacking dystrophin and utrophin exhibit progressive muscular dystrophy, markedly reduced mobility and life span, and severe abnormalities at the neuromuscular and myotendinous junctions (20,30). Since the pathology of skeletal and cardiac muscle of mdx/utrn Ϫ/Ϫ mice more closely resembles that in DMD patients than the pathology of mdx mice, the doubly deficient mouse is a useful and appropriate model for developing and testing new therapies for muscular dystrophy (4,12,13,27,31).In addition to increased utrophin expression, DMD patients and mdx mice also have more ␣ 7 ␤ 1 -integrin (36, 74). Other cytoskeleton-associated proteins in integrin focal adhesions, such as vinculin and talin, are also elevated in mdx mice (44).…”
mentioning
confidence: 99%
“…Qu-Petersen et al demonstrated restoration of dystrophin production in mdx mice (a mouse model of DMD which has a point mutation within its dystrophin gene) after transplantation of allogenic MDSCs [37]. Similar results were obtained by injecting satellite cells, mesoangioblasts and pericytes in high densities in to dystrophic muscle [52,66,67]. More recently, attention is focused on the use of genetically modified MDSCs, e.g.…”
Section: Regeneration Of Skeletal Musclementioning
confidence: 87%